Population differentiation and Wolbachia phylogeny in mosquitoes of the Aedes scutellaris group. - Behbahani, A; Dutton, T; Davies, N; Townson, H; Sinkins, S (2005)
Mosquito species of the Aedes (Stegomyia) scutellaris (Walker) group (Diptera: Culicidae) are distributed across many islands of the South Pacific and include major regional vectors of filariasis, such as Aedes polynesiensis (Marks). Analysis of populations of Ae. polynesiensis at the extremes of its range, from Fiji and from Moorea, French Polynesia, using the rDNA ITS2 (internal transcribed spacer 2) region and six microsatellite markers showed considerable genetic differentiation between them (F(ST) = 0.298-0.357). Phylogenetic analysis of the Wolbachia endosymbionts in three members of the complex revealed that based on the wsp gene they are all very similar and belong to the Mel subgroup of the A clade, closely related to the Wolbachia strain present in the gall wasp Callyrhytis glandium (Giraud) (Hymenoptera: Cynipidae). By contrast they are only distantly related to the A-clade Wolbachia in Aedes albopictus (Skuse), a species closely allied to the Ae. scutellaris group. There was very low differentiation between the Wolbachia in the Moorea and Fiji populations of Ae. polynesiensis.